The role of immunotolerance in immunosuppressive therapy after liver transplantation - E. Yu. Anosova; I. A. Poludkin; B. I. Kazymov (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье, 2024)
Relevance. Some achievements related to liver transplantation in the field of infectious complications, rejection treatment and surgical tactics have also contributed to improving patient survival. Nevertheless, it is true that the huge progress made in the field of transplantation is mainly due to the emergence of safe and effective immunosuppressive drugs. But complications from immunosuppressive drugs are still a significant problem and the ability to give up immunosuppressants altogether or significantly reduce the dose will help solve it. Aim: to present a review of the literature and to analyze the main aspects of immunotolerance in immunosuppressive therapy after liver transplantation. Materials and methods: Foreign and Russian literature on the topic of immunotolerance and immunosuppressive therapy was used. The search for literary data was carried out in international databases (PubMed/MedLine, ResearchGate), as well as in the scientific electronic library of Russia (eLIBRARY.RU ) for the period 2019– 2024. Conclusion. Undoubtedly, the rejection of immunosuppressive therapy is a brilliant prospect for recipients not only of the liver, but also of other donor organs, therefore, with the future development of interdisciplinary and multifactorial research, the use of various new experimental methods may provide more opportunities and theoretical guidance to find a way to achieve tolerance in liver transplantation.